Desenvolvimento local e a construção de uma nova territorialidade: a implantação do Programa Territórios da Cidadania no norte pioneiro do Paraná - Lopes, Eliana Barreto De Menezes [UNESP]; Kerbauy, Maria Teresa Miceli [UNESP] (My University, 2010)
The territorial approach of development took an important place in the public politics of the State, also guiding the actions originated from different organizations of the society. The territorial focus, infl uenced by the analysis related to the industrial districts, is highlighted as a specifi c form to dealing with process and situations spatially delimited. In Brazil, the Secretary of Territorial Development, linked to the Ministry of Agrarian Development, since 2003, has adopted it strategically through the Programa Nacional de Desenvolvimento Sustentável dos Territórios Rurais (PRONAT). In 2008, had occurs the implantation of the Programa Territórios da Cidadania, a part of the PRONAT and of the rural development politic directed to the dynamization of the depressed territories constituted by small counties that cover rural and urban areas and activities, overcoming the focus on the rural world. The analysis of the assumptions underlying to the adoption of this strategy on the politic of the rural development in Brazil made through the study of the constitution of the Território Integração Norte Pioneiro (PR), which indicates that the focus of this politic falls more on the effectiveness of the decentralization than the concretization, and implementation, of the social management.

A abordagem territorial do desenvolvimento assumiu lugar de destaque nas políticas públicas estatais, norteando também ações origináarias de distintas organizações da sociedade. O enfoque territorial, infl uenciado pelas análises relacionadas aos distritos industriais, destaca-se como uma forma específi ca de tratar processos e situações delimitadas espacialmente. No Brasil, a Secretaria de Desenvolvimento Territorial, vinculada ao Ministério do Desenvolvimento Agrário, desde 2003, o adota-o estrategicamente por meio do Programa Nacional de Desenvolvimento Sustentável dos Territórios Rurais (PRONAT). Em 2008, ocorreu a implantação do Programa Territórios da Cidadania, um desdobramento do PRONAT e das políticas de desenvolvimento rural direcionadas à dinamização de territórios deprimidos, constituídos por pequenos municípios e que, compreendem áreas e atividades rurais e urbanas, superando a ênfase setorial do mundo rural. A análise dos pressupostos subjacentes à adoção dessa estratégia nas políticas de desenvolvimento rural no Brasil, realizada por meio do estudo da constituição do Território Integração Norte Pioneiro (PR), indica que a ênfase dessa política recai mais sobre a efetividade da descentralização do que a concretização da gestão social.
Keywords: Territories; Territorial approach on development; PRONAT; Programa Territórios da Cidadania; Território Integração Norte Pioneiro; Territórios; Abordagem territorial do desenvolvimento; PRONAT; Programa Territórios da Cidadania; Território Integração Norte Pioneiro